Venlafaxine Extended Release in the Treatment of Post Herpetic Neuralgia: A Quasi-Experimental Study (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Anti depressant drugs are sometimes used to treat neuropathic pain like Postherpetic Neuralgia (PHN) however, their analgesic efficacy is unclear. Venlafaxine is a reasonably well tolerated anti depressant and is a Serotonin Norepinephrine Reuptake Inhibitor (SNRI) and weak noradrenaline reuptake inhibitor. Although not licensed for the treatment of chronic or neuropathic pain in most countries, it is sometimes used for this indication. The present study evaluated the efficacy, tolerability and Quality of Life (QoL) of venlafaxine use for 12 weeks in patients with PHN.Materials and methods: This quasi-experimental (Pretest-posttest design) was conducted in the department of Neurology, Dhaka Medical College Hospital, from July 2012 to June 2013. Four hundred and fifty two patients were included in the study and Venlafaxine extended release tablet (75 to 150 mg) were administeredfor 12 weeks. Pain severity score, pain interference score and QoL score were assessed by a self-rated questionnaire before treatment and at 12 weeks follow-up.Results: Majority of the patients were male (63.7%) with a mean age of 48.1 years. After 12 weeks of Venlafaxine treatment, 330 (73%) patients reported at least 50% relief in pain, whereas three (0.7%) patients did not report any pain relief. Pain was relieved completely in 32 (7.0%) patients. There was a significant decrease in the mean pain severity score, (5.8±2.0 versus 3.6±2.2) and meanpain interference score (4.5±2.0 versus 3.1±1.9) from baseline to 12 weeks. The mean QoL scale score improved significantly from 5.9±1.6 at baseline to 8.0±1.7 at week 12. Only 2.8% (13/452) patients experienced at least one adverse effect during the study period.Conclusion: Venlafaxine was found to be effective, safe and well tolerated in the patients of PHN for relieving pain and improving QoL. Further double blinded randomize study is needed to validate these findings.JCMCTA 2021 ; 32 (1) : 31-34